PENGARUH MOTIVASI KERJA, DISIPLIN KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA PERAWAT RSUD JOMBANG - Wahyu Juli Iswanto; Eka Askafi; Supriyono Supriyono (FKDP (Forum Komunikasi Dosen Peneliti), 2020)
This study aims to determine (1) the influence of work motivation on the performance of nurses in Jombang hospital, (2) the effect of work discipline on the performance of nurses in Jombang hospital, (3) the influence of the work environment on the performance of nurses in Jombang hospital, (4) the effect of work motivation, work discipline, and work environment on the performance of nurses in Jombang hospital. Data collection methods used in this study used a questionnaire. The population taken is nurses in Jombang district general hospital internal medicine room totaling 65 nurses with the details of abhanyu room 20 nurses, sadewa room as many as 25 nurses, and nakula as many as 25 nurses. The samples in this study were taken from nurses in the internal medicine room totaling 40 nurses from abimanyu and sadewa rooms. Data were analyzed using descriptive statistics, prerequisite tests, multiple linear regression analysis. The results of this study indicate that it is included in the type of quantitative research. Quantitative data analysis used was multiple linear regression and using SPSS version 24.0 (1) the effect of work motivation, work discipline, and work environment on the performance of nurses in Jombang hospital, with the work motivation regression coefficient 0, 086, the value of the work discipline coefficient of 0.215 and the value of the work environment regression coefficient of 0.245 and f arithmetic> F table (7.393> 2.86), (2) work motivation does not have a positive effect on the performance of nurses with a significance value of 0, 550 and t-count value less than the table value (0.604 <2.028), (3) work discipline does not have a positive effect on the performance of nurses with a significance value of 0, 144, and tcount less than ttable (1.495 <2.028), (4) work environment has a positive effect on nurses' performance with a significance value of 0, 072, and tcount is less than the table value (1.855 <2.028).